New standard of evidence and safety in the parathyroid surgery - P. N. Romashchenko; N. A. Maistrenko; D. S. Krivolapov; D. O. Vshivtsev (Вестник хирургии имени И.И. Грекова)
The paper presents a clinical case that reflects difficulties of primary hyperparathyroidism diagnosis, as well as an experience of usage of new methods in parathyroid surgery, which aims at increasing degree of evidence and safety of interventions. The sequence of the implemented methods of laboratory and instrumental examination made it possible to identify the accurate location of parathyroid adenomas, and realization of the proposed surgical tactics - to perform a surgical intervention justified in terms of volume and methodology, to avoid postoperative complications and improve the patient's quality of life.